2010
DOI: 10.1111/j.1365-3059.2010.02385.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and non‐pathogenic Agrobacterium tumefaciens, A. rhizogenes and A. vitis strains form biofilms on abiotic as well as on root surfaces

Abstract: Pathogenic and non-pathogenic Agrobacterium tumefaciens, A. rhizogenes and A. vitis strains growing in minimal liquid medium adhered to different abiotic surfaces, forming biofilms at initial stages of development. Agrobacterium tumefaciens and A. vitis strains were able to attach to both polystyrene and polypropylene materials, whereas the A. rhizogenes strains only bound to polystyrene surfaces. Strains of the three species were also able to form biofilms on borosilicate coverslips. It is concluded that thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…We have recently shown that the biocontrol agent R. rhizogenes (formerly A. radiobacter [56]) strain K84 is able to form biofilms not only on abiotic surfaces but also on plant root surfaces, where biofilms become complex and structured, with cells adhering to the surface and to each other (1). Based on these observations, we…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently shown that the biocontrol agent R. rhizogenes (formerly A. radiobacter [56]) strain K84 is able to form biofilms not only on abiotic surfaces but also on plant root surfaces, where biofilms become complex and structured, with cells adhering to the surface and to each other (1). Based on these observations, we…”
Section: Discussionmentioning
confidence: 99%
“…In the first, large-scale screen, 10 l of overnight cultures in MG/L liquid medium was added to 200 l of ATM liquid medium in 96-well microtiter polypropylene plates, using one well per mutant. The amounts of planktonic (optical density at 570 nm [OD 570 ]) and surface-attached (A 570 ) cells were determined by a standard crystal violet (CV) assay after static incubation for 48 h at 26°C (1,39). Each potential mutant that was compromised in terms of biofilm formation in this first screen was then rescreened by individually adjusting the ATM culture to an OD 570 of 0.04, and growth was continued in microtiter plates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations